A Human Osteocyte Cell Line Model for Studying Staphylococcus aureus Persistence in Osteomyelitis - Gunn, Nicholas J.; Zelmer, Anja R.; Kidd, Stephen P.; Solomon, Lucian B.; Roscioli, Eugene; Yang, Dongqing; Atkins, Gerald J. (Frontiers in Cellular and Infection Microbiology, 2021)
Infectious osteomyelitis associated with periprosthetic joint infections is often recalcitrant to treatment and has a high rate of recurrence. In the case of Staphylococcus aureus, the most common pathogen in all forms of osteomyelitis, this may be attributed in part to residual intracellular infection of host cells, yet this is not generally considered in the treatment strategy. Osteocytes represent a unique cell type in this context due to their abundance, their formation of a syncytium throughout the bone that could facilitate bacterial spread and their relative inaccessibility to professional immune cells. As such, there is potential value in studying the host-pathogen interactions in the context of this cell type in a replicable and scalable in vitro model. Here, we examined the utility of the human osteosarcoma cell line SaOS2 differentiated to an osteocyte-like stage (SaOS2-OY) as an intracellular infection model for S. aureus. We demonstrate that S. aureus is capable of generating stable intracellular infections in SaOS2-OY cells but not in undifferentiated, osteoblast-like SaOS2 cells (SaOS2-OB). In SaOS2-OY cells, S. aureus transitioned towards a quasi-dormant small colony variant (SCV) growth phenotype over a 15-day post-infection period. The infected cells exhibited changes in the expression of key immunomodulatory mediators that are consistent with the infection response of primary osteocytes. Thus, SaOS2-OY is an appropriate cell line model that may be predictive of the interactions between S. aureus and human osteocytes, and this will be useful for studying mechanisms of persistence and for testing efficacy of potential antimicrobial strategies.